Stick–slip phenomena in the friction of human skin - Derler, S.; Rotaru, G.-M. (Wear, 2013)
The stick–slip behaviour of the index finger pad sliding on wet, smooth glass was investigated as a function of normal force and sliding velocity in friction measurements using a tri-axial force plate. The friction coefficients during stick–slip (0.53±0.21) were found to be typically 30% lower than those of stationary sliding (0.78±0.35). Stick–slip friction either occurred continuously throughout entire friction measurements or alternated with stationary sliding phases. During stick–slip the amplitude of the friction coefficient generally varied more than ±25% about the mean, whereas stationary sliding was characterized by variations smaller than ±10%. The load-dependence of the overall friction coefficients as well as those for stationary sliding and stick–slip friction was in agreement with the adhesion friction model. In addition, the friction coefficients decreasing with increasing sliding velocity indicated friction in the mixed lubrication regime. Results obtained on stick–slip friction of the finger pad might be useful in connection with the development of artificial skin in robotics and for the control of stick–slip friction between precision tools and soft tissue.